2014
DOI: 10.1007/s12560-014-9161-5
|View full text |Cite
|
Sign up to set email alerts
|

A One Year Study on the Concentrations of Norovirus and Enteric Adenoviruses in Wastewater and A Surface Drinking Water Source in Norway

Abstract: Enteric viruses transmitted via the faecal-oral route occur in high concentrations in wastewater and may contaminate drinking water sources and cause disease. In order to quantify enteric adenovirus and norovirus genotypes I and II (GI and GII) impacting a drinking source in Norway, samples of surface water (52), wastewater inlet (64) and outlet (59) were collected between January 2011 and April 2012. Samples were concentrated in two steps, using an electropositive disc filter and polyethylene glycol precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 39 publications
8
23
0
Order By: Relevance
“…The median levels of AdV found in influent samples from the two plants were not statistically different and GC per liter varied between 5.0 9 10 4 and 1.1 9 10 7 (median 1.2 9 10 6 ). This level, which was significantly higher during January-March, was quite similar to what has been found in Norway and other studies (Grondahl-Rosado et al 2014;Katayama et al 2008). The NV and AdV levels in raw sewage in the two Norwegian studies, conducted 3 years apart, are quite comparable.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The median levels of AdV found in influent samples from the two plants were not statistically different and GC per liter varied between 5.0 9 10 4 and 1.1 9 10 7 (median 1.2 9 10 6 ). This level, which was significantly higher during January-March, was quite similar to what has been found in Norway and other studies (Grondahl-Rosado et al 2014;Katayama et al 2008). The NV and AdV levels in raw sewage in the two Norwegian studies, conducted 3 years apart, are quite comparable.…”
Section: Discussionsupporting
confidence: 89%
“…In plant A, the median levels of log 10 GC/l were 6.2 (GI) and 6.5 (GII), while in B, the median concentration was 5.9 and 6.2, for GI and GII, respectively. These values are at the same level as was found in a Norwegian study in 2011-2012, but [1.6 log 10 higher than what was found in an Irish study in 2009-2010 in a WWTP of approximately the same size as plant B (Flannery et al 2012;Grondahl-Rosado et al 2014). In all three studies, the highest levels were found for GII; however, the differences were not significant in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…However, limited quantitative data are available for the levels of human NoV present in surface water and groundwater. Analysis of river water in France and Norway showed that human NoV GI and GII were present at levels of 10 2 to 10 3 RNA copies/liter (71,72). Further investigation into the levels of human NoV in irrigation water, as well as determination of the minimum level of human NoV leading to internalization in fresh produce, can help to elucidate the occurrence of this phenomenon during field production of fresh produce.…”
Section: Discussionmentioning
confidence: 99%
“…This group includes various types of enteroviruses (including poliomyelitis virus), ECHO (enteric cytopathic human orphan), Coxsackie A and B viruses, the causative agent of viral hepatitis A, adenovirus, reovirus, rotavirus, etc. [2][3][4]. Viruses may be proven by cultivation on cell culture or by molecular biological methods (polymerase chain reaction -PCR).…”
Section: Introductionmentioning
confidence: 99%